Dive Patterns of Belugas (Delphinapterus leucas) in Waters Near Eastern Devon Island - Heide-Jørgensen, M.P.; Richard, P.R.; Rosing-Asvid, A. (ARCTIC, 1998)
Data were obtained for six belugas or white whales (Delphinapterus leucas) instrumented with satellite-linked dive recorders in September-November 1995 in waters near eastern Devon Island, Canada. The mean of the daily maximum depths of dives was 483-665 m for the 31-51 days when maximum depth measurements were taken. The deepest dive recorded was 872 m. Both the dive rate (number of dives per hour to depths > 8 m) and the time at surface (time spent within the uppermost 5 m of the water column) declined from mid-September through mid-October. The four females had significantly elevated dive rates during the nights (2300-0500), whereas the males showed no effects of time of day on the dive rates. Few dives lasted more than 18 min, and most lasted either less than 1 min or for 9-18 min. A trend from short dives to longer dives was noted from mid-September through October, along with a decline in the number of dives to 8-20 m and a corresponding increase in the number of dives to 200-452 m during the same period. The small whales made more dives and had longer times at the surface than the large whales, but they did not dive as deeply or for as long periods as did the large whales. Vertical speeds ranged from .05 ms to .19 ms for depths of 52-800 m. These speeds are significantly faster than vertical speeds recorded from narwhals (Monodon monoceros). En septembre-novembre 1995, on a recueilli des données sur six bélugas ou dauphins blancs (Delphinapterus leucas) équipés d'enregistreurs de plongée en liaison avec un satellite, dans les eaux proches de la partie est de l'île Devon au Canada. La moyenne quotidienne de la profondeur maximale des plongées était de 483 à 665 m pour les 31 à 51 jours durant lesquels on a mesuré la profondeur maximale. La plongée la plus profonde enregistrée était de 872 m. De mi-septembre à mi-octobre, le taux de plongée (nombre de plongées par heure à des profondeurs > à 8 m), de même que le temps en surface (temps passé dans les 5 m supérieurs de la colonne d'eau) ont diminué. ...